2006
DOI: 10.1021/ja056301w
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution in a Hydrothermal Reaction between Nb2O5and NaOH Solution:  From Nb2O5Grains to Microporous Na2Nb2O6·2/3H2O Fibers and NaNbO3Cubes

Abstract: Niobium pentoxide reacts actively with concentrate NaOH solution under hydrothermal conditions at as low as 120 degrees C. The reaction ruptures the corner-sharing of NbO(7) decahedra and NbO(6) octahedra in the reactant Nb(2)O(5), yielding various niobates, and the structure and composition of the niobates depend on the reaction temperature and time. The morphological evolution of the solid products in the reaction at 180 degrees C is monitored via SEM: the fine Nb(2)O(5) powder aggregates first to irregular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
135
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(148 citation statements)
references
References 56 publications
10
135
2
1
Order By: Relevance
“…Zhu et al reported that NaNbO 3 was synthesized from Nb 2 O 5 and NaOH aqueous solution by a hydrothermal process. 8) In this process, a high-pressure condition is required. Recently, some oxide superconductors were synthesized by a molten hydroxide route at low temperatures.…”
Section: )4)mentioning
confidence: 99%
“…Zhu et al reported that NaNbO 3 was synthesized from Nb 2 O 5 and NaOH aqueous solution by a hydrothermal process. 8) In this process, a high-pressure condition is required. Recently, some oxide superconductors were synthesized by a molten hydroxide route at low temperatures.…”
Section: )4)mentioning
confidence: 99%
“…However, for the NN synthesis, sodium hexaniobates was precipitated by its low solubility in highly concentrated NaOH solution. 33,46) As shown in Fig. 4(a)-(f), the NN particle mean sizes are once decreased from ca.…”
Section: Preparation Of Nn Fine Particles: Effects Of Naohmentioning
confidence: 73%
“…Nano-size alkali niobate particles with cubic morphology could be obtained at low temperature (<200°C) by hydrothermal method. 14 23) In this study, we synthesized NaNbO 3 (NN) nanoparticles by the solvothermal method in 1,4-butanediol as a solvent. Since use of nanoparticle reduces the sintering temperature, NN dense ceramics were fabricated using the solvothermally-synthesized NN nanoparticles and the piezoelectric properties were evaluated.…”
Section: )6)mentioning
confidence: 99%